The Effect of Regional Expenditure, Population Density, HDI, and Ict-Di Toward Environmental Performance Index of 34 Provinces in Indonesia - Latifatul Muta’arofah; Fafurida (Efficient: Indonesian Journal of Development Economics, 2024)
This study aims to analyze the effect of Regional Expenditure, population density, HDI, and ICT-DI on the Environmental Performance Index of 34 provinces in Indonesia 2017-2021. The method of this study used panel data regression with Fixed Effects Model approach using Generalized Least Square. Cross sections of this study are 34 provinces in Indonesia with time series from 2017 to 2021 (5 years). Variables in this study consist of independent variables, such as Regional Expenditure, population density, HDI, and Information and Communication Technology Development Index (ICT-DI), and Environmental Performance Index as dependent variable. The results of this study indicate that all variables affect the Environmental Performance Index simultaneously. In partial effect, variables of Regional Expenditure and population density have negative and significant effect on the Environmental Performance Index. While HDI and ICT-DI partially have positive and significant effect on the Environmental Performance Index using significance level of 5%.